Improving Communication Ability of a Child with Selective Mutism Through “Kita Semua Sahabat” Training - Puspita Adhi Kusuma Wijayanti; Murtini Murtini (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Selective Mutism (SM) is characterized by failure to speak at some period of time in specific social situations (e.g., at school), but can talk in other familiar situations (home). This study aimed to determine the effectiveness of ‘Kita Semua Sahabat’ in improving communication skills in children with SM. The subject was a 5 year-old boy who had been diagnosed based on DSM-V. The research design was a single case experimental design. Interventions were performed using the technique of stimulus fading and contingency management which were packed through the training of ‘Kita Semua Sahabat’. The result showed that there was a significant increase, and communication with stimulus (prompts) had a greater increase than communication without stimulus (child’s initiation). The research showed that Training ‘Kita Semua Sahabat’ is effective to increase communication among children with SM, and more frequent verbal communication happens if more stimuli were given to the child.